Negosiasi Relasi Gender dalam Keluarga Bapak Rumah Tangga dan Buruh Perempuan PT. Taekwang Kabupaten Subang - Cindy Veronika Sihombing; Arianti Ina Restiani Hunga; Rizki Amalia Yanuartha (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
This study analyzes the negotiation of gender relations in stay-at-home father families among female workers employed at PT. Taekwang in Subang. The study aims to examine the conditions that drive changes in gender roles, the negotiation process surrounding the division of domestic work and childcare, and the ways in which stay-at-home fathers interpret their roles within a patriarchal culture. This study employs a qualitative approach with a case study design. The primary informants consisted of eight individuals, representing four married couples selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and were subsequently analyzed thematically using Marxist-Socialist Feminist Theory and the concept of hegemonic masculinity. The findings indicate that gender-role transformation is influenced by husband employment instability, wives employment opportunities in the industrial sector, work flexibility, and childcare needs. Husbands assume greater responsibility for domestic work and childcare, while wives play a more dominant role in providing for the household economy. However, the negotiation process results in only a partial redistribution of reproductive labor, as wives continue to perform some domestic tasks, while the male-breadwinner norm and social stigma toward stay-at-home fathers persist. These findings demonstrate that the transformation of gender relations occurs through a dynamic negotiation involving economic conditions, social reproductive labor, power relations, and the construction of masculinity.